Students' Oral Communication Skills in Using Digital Encyclopedia of Mammals Based on Citizen Science Project - Fitri Aryanti; Topik Hidayat; Yayan Sanjaya; Kusnadi Kusnadi (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
This study aimed to analyze students' oral communication skills using the Citizen Science Project (CSP) based digital encyclopedia of mammals in learning. This research combines digital technology, community involvement, and the development of scientific communication skills as a novelty. The method used was descriptive quantitative with data collection techniques through observation. The research subjects consisted of 30 prospective teacher students of the Biology Education Study Program at a private university in Bandung. The instrument used was an observation sheet on oral communication skills. The results showed that most students scored good or sufficient. The average value on indicators 1-6, namely being able to provide information or ideas by 75%, including the good category, mastering the material to be used as presentation material by 70%, including the sufficient category, delivering report results systematically and clearly by 75% including the good category, questioning skills by 70% including the sufficient category, being able to answer questions by 75% including the good category, and confidence by 70% including the sufficient category. The percentage value of the active indicator in group discussions is 95%, which is included in the very good category. Based on these data, communication skills are critical because they allow students to convey ideas, work together, and exchange information. Students' oral communication skills can be improved by continuing to train and provide opportunities for students to communicate orally on an ongoing basis based on CSP.